Features of charge pairs recombination in the track regions of organic solid scintillators - Tarasenko, O.A. (Functional Materials, 2012)
Some features of the recombination of charge states generated in organic solid scintillators for different densities of radiation excitation, as well as the effect of the polarization mechanisms on this process are studied. The estimations are made for single crystals of stilbene and p-terphenyl, and a plastic scintillator. The influence of anisotropy of the dielectric characteristics on the processes under investigation is considered for an anthracene single crystal. The estimated values of the average distance d between the centers of charge pairs (M₊, M₋), generated in a charged particle track, are compared with the value of the radius of stable polarization environment r, created by an excess charge carrier in an organic condensed medium. It is shown that an influence of the polarization on the recombination mechanism of the charge state pairs, which is produced by the ionizing radiations with different specific energy loss dE/dx, grows for high local density in the track volume. The estimations that we obtained are in a good agreement with the results of the light yield measurements of organic solid scintillators.